2006
DOI: 10.1007/s10591-006-9007-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing Strategic Family Therapy: Insights from a Dynamic Systems Perspective

Abstract: As one of the more mature marriage and family therapy (MFT) models, strategic family therapy has a distinguished and colorful history. Part of that history includes an era when strategic therapy was considered by some to be manipulative and even unethical. Recent advances in our understanding of the behavior of complex natural systems via dynamic systems theory may shed new light on the process of strategic family therapy and help us understand more fully the underlying purposes of the preferred therapeutic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The overarching goal of strategic therapy is to encourage the marital relationship to change the distinct behavioral patterns associated with the identified problem (Gardner, Burr, & Weidower, 2006; Thomas, 1992). In the case study couple, the distinct behavioral patterns associated with the identified problem were as follows: each person was to adhere to the societal gender norm expressions; the relationship would maintain a sense of homeostasis if each person would remain inauthentic; and problems were too anxiety provoking to be addressed so acting out behavior was seen as more permissive.…”
Section: Strategic Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…The overarching goal of strategic therapy is to encourage the marital relationship to change the distinct behavioral patterns associated with the identified problem (Gardner, Burr, & Weidower, 2006; Thomas, 1992). In the case study couple, the distinct behavioral patterns associated with the identified problem were as follows: each person was to adhere to the societal gender norm expressions; the relationship would maintain a sense of homeostasis if each person would remain inauthentic; and problems were too anxiety provoking to be addressed so acting out behavior was seen as more permissive.…”
Section: Strategic Therapymentioning
confidence: 99%
“…Within the third phase of strategic therapy, the counselor’s focus became the couple’s communications, because people are always communicating. In essence, problems are believed to be a result of how the clients are communicating with one another through content and command messages (Gardner et al, 2006; Metcalf, 2011; Riley, 1990). The couple benefits when the counselor views the couple’s problems and symptoms as a result of how the couple is communicating with one another (Smith et al, 2011).…”
Section: Strategic Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…It could be said that the strategic family therapist is seeking to perturb the family's dynamic patterns of interaction in the hopes that the family will move from the attractor state that maintains the problem to a new state that alleviates the family's symptoms. As dynamic systems theory is beginning to be applied to models of individual and family psychotherapy (e.g., Gardner et al 2006), clinicians who work with complex relationship systems are encouraged to evaluate the potential contributions such a perspective may offer their practice.…”
Section: For Practitionersmentioning
confidence: 99%